Community Violence Exposure is Associated with Hippocampus–Insula Resting State Functional Connectivity in Urban Youth. (1st August 2021) - Reda, M.H.; Marusak, H.A.; Ely, T.D.; van Rooij, S.J.H.; Stenson, A.F.; Stevens, J.S.; France, J.M.; Tottenham, N.; Jovanovic, T.
Highlights: Childhood violence exposure is associated with hippocampal circuitry. Hippocampus – insula functional connectivity is linked to childhood adversity. Community violence is a unique predictor of altered threat circuitry. Accelerated maturation of threat circuitry in youth with violence exposure. Abstract: Our previous work has linked childhood violence exposure in Black youth to functional changes in the hippocampus, a brain region sensitive to stress. However, different contexts of violence exposure (e.g., community, home, school) may have differential effects on circuitry. We investigated the unique effect of community violence in predicting resting-state functional connectivity (rsFC) in the hippocampus. Fifty-two (26F) violence-exposed Black youth ages 8–15 performed resting-state functional neuroimaging scans while looking at a fixation cross for seven minutes with eyes open. Seed-based analyses were conducted to examine the association between total violence exposure and rsFC of the hippocampus to the whole brain. Follow-up hierarchical regression analysis were performed to specifically investigate community violence. Violence exposure was associated with higher hippocampus rsFC with a core node of the Default Mode Network (i.e., posterior cingulate cortex) and lower hippocampal rsFC with a core node of the Salience Network (i.e., insula). Community violence uniquely associated with lower hippocampus–insula rsFC, after controlling for home and school violence, sex and age. Age-related decreases in hippocampus–insula rsFC were also present in youth with lower violence exposure, but not in youth with higher violence exposure. This is one of the first studies to investigate the unique impact of community violence, above home and school violence, on threat circuitry. Our data suggest functional alterations in the hippocampus in violence-exposed youth, and that violence in the community may be a more salient form of threat exposure compared to other forms of violence experienced by youth.